Pelatihan Pembuatan Model Test Kapal untuk Pengujian Hidrodinamika Bagi Mahasiswa Teknik Konstruksi Perkapalan - Yasim, Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Hydrodynamic testing is a crucial stage in ship design to ensure vessel performance and safety in accordance with design criteria. This testing is commonly conducted using small-scale ship models that must satisfy the principles of geometric, kinematic, and dynamic similarity. However, students of the Shipbuilding Engineering Study Program at the University of Jember have limited understanding and practical skills in constructing ship testing models, which may affect the quality of resistance and seakeeping experiments. This training activity aimed to enhance students’ knowledge and skills in developing ship testing models that comply with hydrodynamic principles. The activity was implemented through a structured training program covering ship design, including three-dimensional modeling, two-dimensional lines plan preparation, scale determination, detailed design, and cutting plan development, followed by model construction stages such as frame marking and cutting, structural assembly, hull fabrication, finishing, and final model preparation. The results indicate improved student competence in producing ship testing models with appropriate shape and scale accuracy, making them suitable for hydrodynamic laboratory experiments and supporting other academic activities such as research and fast boat competitions.